20 years of Malaria notifications in Bologna AUSL. (30th September 2020) - Canal, V; Ubiali, A; Resi, D; Pandolfi, P; Fantini, M P
Abstract: Background: Notification of confirmed or suspected cases of Malaria is compulsory in Italy. It is essential to optimize control measures in case of imported and indigenous events, considering that the main local vector, Anopheles labranchiae, is still present in Italy. Methods: Descriptive analysis of malaria cases notified from Bologna local health authority (AUSL) from January 2000 to December 2019. Results: In the period 2000-2019, out of the 248 Malaria cases notified to the AUSL, 161 were males, and 87 were females, with median age of 33 (IQR: 42-25). All the cases were sporadic and travel-related. The main reasons for travelling were: return to the country of origin (n = 139, 56, 0%), tourism (n = 39, 15, 7%), work (n = 30, 12, 1%), and immigration (n = 13, 5, 2%). 86 (34, 7%) cases were born in Italy, 43 (17, 3%) in Nigeria, 27 (10, 9%) in Cameroon, and 17 (6, 9%) in Ghana. The cases were imported from Nigeria (n = 56, 22, 9%), Cameroon (n = 30, 12, 2%), Ghana (n = 26, 10, 6%), Ivory Coast (n = 24, 9, 8%). Most of the cases were not taking any drug for Malaria chemoprophylaxis (n = 214, 86, 6%), 20 cases (8, 1%) properly completed the prophylaxis, while 13 cases (5, 3%) started chemoprophylaxis but they didn't complete it. The etiological agent identified was Plasmodium falciparum in 176 cases (71, 0%), P. vivax in 26 cases (10, 5%). Among the former cases 49 (32, 2%) were contracted in Nigeria, 29 (19, 1%) in Cameroon, 23 (15, 1%) in Ghana, 20 (13, 2%) in Ivory Coast, 10 (6, 6%) in Senegal. 11 (68, 8%) cases of P. vivax were contracted in Pakistan. Conclusions: Epidemiological data collected from Bologna AUSL are consistent with those described from Istituto Superiore di Sanità: the majority of cases was comprised of foreigners, the great majority of cases was imported from Africa. P. Falciparum was prevalent in Africa while P. vivax was prevalent in Asia. Key messages: The knowledge of the epidemiological situation allows public health workers to advise international travelers focusing on those most at risk of contracting Malaria. Periodic assessment of local epidemiology is necessary to evaluate if data are consistent with those described from international literature.